A bat in the belfry : a home repair is homicide mystery - Graves, Sarah, 1951- (Graves, Sarah, 1951- Home repair is homicide mystery., 2013)
It is nearly midnight when the enormous bell in the belfry of All Faith Chapel - silent for decades - booms forth, startling awake the entire town of Eastport. Upon inspection of the steeple, the police uncover the body of local teenager Karen Hansen, who had climbed the belfry's dark, rickety stairs for a midnight rendezvous. But instead of the promise of an exciting new life, Karen meets her death. Meanwhile, as an epic nor'easter bears down on the idyllic island town, Jake Tiptree hurries to shore up her ramshackle old house against the big blow. An amateur detective, she has sworn off chasing criminals. But when the news of Karen's murder spreads and much of the evidence points to Jake's likable houseguest, she and her sleuthing partner, Ellie White, get to work. They discover an unexpected ally in newcomer Lizzie Snow, a woman from "away" who seemed to have blown into town with the nor'easter, and who also seems to know a lot about the mind of a killer. Can Jake and Ellie trust her? As a killer roams free and the townsfolk struggle against the pounding, screaming storm, the resulting tempest of gossip and suspicion rivals anything the Atlantic could brew up - and threatens to keep Jake and Ellie from putting the final nail in this cold-blooded case.